Comparison of Immediate and Sequential Withdrawal of a Systemic Glucocorticoid in the Treatment of Acute Exacerbations of Chronic Obstructive Pulmonary Disease: A Multicenter, Randomized, Double-Blind, Parallel-Controlled, Open-Label Study - Zhou, Ling; Fang, Yuanyuan; Liu, Wei; Zhang, Jianchu; Wang, Yingnan; Xie, Sheng; Zhong, Minhua; Wang, Zhengyan; Li, Guangcai; Ai, Hongyan; Guo, Hongrong; Zeng, Fanjun; et al. (Frontiers in Molecular Biosciences, 2021)
Patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD) were treated with immediate or sequential withdrawal after five days of systemic glucocorticoids. The effects of the two withdrawal methods on the prognosis of patients were compared at 30, 90, 180, and 360 days after discharge. The study was completed in August 2020 and is registered at the China Clinical Trials Registry (Chictr.org) (ChiCTR1800018894). According to general data and clinical characteristics, there were no significant differences (P > 0.05) between the 329 patients in the immediate withdrawal group and the 310 patients in the sequential withdrawal group. At the 30-day follow-up, the acute exacerbation frequency ,the rehospitalization rate were no significant difference two groups . mMRC) and CAT scores were also not significantly different between the two groups. At the 90-day follow-up and 180-day follow-up, acute exacerbation frequency, rehospitalization rate, mortality, and ICU treatment rate were not significantly different between the two groups. In addition,FEV1%,PEF, and mMRC and CAT scores were not significantly different. At the 360-day follow-up, the acute exacerbation frequency ，the time of stay in the hospital ，FEV1%, PEF, and mMRC and CAT scores were also not significantly different. The time from discharge to first acute exacerbation was significantly lower (P < 0.05) in the immediate withdrawal group (46.12 days) than in sequential withdrawal group (49.02 days).Subgroup analysis was performed according to age, degree of disease, and relevant indicators. At the 30-day follow-up, the acute exacerbation frequency of patients with advanced age, high global strategy for chronic obstructive lung disease (GOLD), and high fractional exhaled nitric oxide was significantly higher (P < 0.05) in the immediate withdrawal group than in the sequential withdrawal group. In addition, according to receiver operating characteristic curve analysis, the frequency of acute exacerbations was significantly higher in patients with age > 63.5 years or GOLD > 3 in the immediate withdrawal group than in the sequential withdrawal group, suggesting that the short-term efficacy was poor.AECOPD patients who are elderly or with a high GOLD grade should be treated with glucocorticoid sequential withdrawal to reduce acute exacerbation frequency at the 30-day follow-up.